Singular sensations: marketing to single women - DePaulo, Bella (Henry Stewart Talks, 2009)
Who counts as single?, What do you know about the place of singles in society?, Why so many singles?, Single life in the 21st century, The implications for marketers, Example of product pricing that is singles friendly, What is the economic status of single women?, What do single women have in common?, Marketing mistakes, Singles provide the social glue, Implications to marketers